Study on the long-term curative effect of repeat percutaneous balloon mitral valvuloplasty in patients with mitral restenosis. Issue 32 (August 2019) - Zhang, Ling; Hou, Jiliu; Duan, Yulong; Chen, Junjun; Du, Huijuan; Shi, Zhengang
Abstract : Abstract: To study the long-term curative effect of repeat percutaneous balloon mitral valvuloplasty (PBMV) in patients with mitral restenosis. In our study, mitral restenosis developed in 39 patients after PBMV. Repeat PBMV was performed according to the improved Inoue method. All patients were followed up. Of 39 patients, 36 were successfully treated with repeat PBMV (achievement ratio, 92.3%). Immediately after repeat PBMV, clinical symptoms and left atrial mean pressure (LAP), pulmonary artery systolic pressure (PASP), mitral valve gradient (MVG), and mitral valve orifice area (MVA) improved significantly (24.50 ± 6.54 mmHg vs 9.66 ± 4.21 mmHg for LAP, 1.05 ± 0.19 cm 2 vs 2.23 ± 0.22 cm 2 for MVA, 17.03 ± 4.52 mmHg vs 7.79 ± 4.07 mmHg for MVG, 58.12 ± 12.68 mmHg vs 31.45 ± 10.02 mmHg for PASP; P  <.05). Meanwhile, left atrial end-diastolic dimension (LAD) was altered slightly (4.71 ± 0.75 vs 4.07 ± 0.69, P  >.05). The 36 patients were followed up for 69 ± 23 (12–146) months. After long-term follow-up immediately after repeat PBMV, the results did not show a significant change (2.23 ± −0.22 cm 2 vs 2.02 ± −0.21 cm 2 for MVA, 7.79 ± −4.07 mmHg vs 9.15 ± -4.11 mmHg for MVG; P  >.05) and were approximated to those shortly after repeat PBMV (2.23 ± 0.22 cm 2 vs 2.02 ± 0.21 cm 2 for MVA, 7.79 ± 4.07 mmHg vs 9.15 ± 4.11 mmHg for MVG; P  > 0.05). LAD did not change significantly (4.13 ± 0.71 cm vs. 4.07 ± 0.69 cm; P  >.05). The long-term follow-up results showed that cardiac function and quality of life were significantly improved in most patients. It would be safe for patients with mitral restenosis to undergo repeat PBMV. Appropriate cases should be selected, and treatment should be performed cautiously. Short- and long-term curative effects would be satisfactory. We suggested that repeat PBMV be the first choice for patients with mitral restenosis after first PBMV.